Social program and digital marketing strategy in community development projects in MSME “Sodagar Snack” at Kuningan, East Java - Prita Prasetya; Denzel Da Polla; Derick Philander Santosa; Gabriella Aurielle Wijaya; Khantidhira Winona Suharto; Mohammad Rifki; Stefanus Jason Hajadi; Stelya Clarence Latuperisa; Veronica Lila Novesaria (Privietlab, 2023)
Digitalization has become essential in developing businesses, including Micro, Small, and Medium Enterprises (MSMEs). Community Development program was held in Kuningan, Groupst Java whose focus was on MSMEs,